The uses and gratifications approach on facebook - Siti Azizah (Fakultas Psikologi, 2020)
Technological advances are taking place every day and they are altering the way people communicate with each other. Advances in communication technology, for example, allows the inception of social networking sites. Social networking sites are considered not only a platform for communication, but the are also novel mediums in which individual virtual lives are created and networks with friends, family members, employees and other persons may be formed. The goal of the present article is to review the motivation of social media users, especially facebook users, based on the uses and gratification approach. Four motivations are presented including cognitive, affective, integrative-habitual, and social interractive needs. These needs work interdependently to drive people using social media sites.